EFEKTIVITAS PENERIMAAN DAN KONTRIBUSI PBB-P2 TERHADAP PENDAPATAN ASLI DAERAH KOTA BANJARMASIN SEBELUM DAN SESUDAH PEMBEBASAN SANKSI ADMINISTRASI PBB-P2 DENGAN PENERAPAN PERATURAN WALI KOTA BANJARMASIN NOMOR 31 TAHUN 2021 - Firda Hasna Kamila; Sustinah Limarjani; H. Alfian (Universitas Lambung Mangkurat, 2022)
The purpose of this study is to be able to determine the effectiveness of the receipt and contribution of PBB-P2 to the Banjarmasin City Pad before and after the exemption of UN-P2 administrative sanctions with the application of Banjarmasin Mayor Regulation Number 31 of 2021. Based on the research that has been carried out, it can be seen that the effectiveness of UN-P2 admission before the release of UN-P2 administrative sanctions with the application of Banjarmasin Mayor Regulation Number 31 of 2021 is 119.16% with very effective criteria, while after the release of UN-P2 administrative sanctions with the application of Banjarmasin Mayor Regulation Number 31 of 2021 is lower, namely 111.29% with very effective criteria. Meanwhile, the contribution of PBB-P2 to the Banjarmasin City Pad before the release of UN-P2 administrative sanctions with the application of Banjarmasin Mayor Regulation Number 31 of 2021 was 6.81%, while after the release of UN-P2 administrative sanctions with the application of Banjarmasin Mayor Regulation Number 31 of 2021, it was higher at 8.22%. The exemption of UN-P2 administrative sanctions with the application of Banjarmasin Mayor Regulation Number 31 of 2021 is considered unsuccessful in increasing the effectiveness of UN-P2 revenue, but has succeeded in increasing the contribution of PBB-P2 to banjarmasin city pad